RESEARCH GROUPS IN THE FIELDS OF FOOD AND NUTRITION AND FOOD SCIENCES FROM 2000 TO 2008 IN BRAZIL - Karen Levy Delmaschio (Universidade do Estado do Rio de Janeiro, 2013)
Considering Bourdieu's thoughts we assume that research groups correspond to institutionalized agents that act constructing and challenging the symbolic and material capital in the core of science. Based on Stengers, when dealing with the constitution of scientific domains, we sought to identify and describe studies on "nutrient and eating" and "food". The empirical setting defined for this study corresponds to CNPq's Directory of Research Groups in Brazil, from 2000 to 2008. There, it was possible to identify, according to current procedures, which are based on the predominant area of each research group, according to the Table of Fields of Knowledge, the existence of 299 research groups in the area of "Food Sciences and Technology" and 171 groups in the area of "Nutrition" in 2008. Distinctly, we used keywords search associated with these scientific fields. We found research groups corresponding to the double of the number provided by CNPq. This mapping enabled to view more clearly some forces in motion in both fields. We highlight the possibility of viewing the research groups that make up the social space of knowledge and know-how production and human development in research on food, which is not clear in the information provided by CNPq. By valuing more interdisciplinary approaches, we understand that there is a need to review the Table of Fields of Knowledge as well as the names and composition of the decision-making bodies on scientific fields in order to include and facilitate the institutional consolidation of the scientific field of "Food and Nutrition" in Brazil.